2017
DOI: 10.17743/jaes.2016.0063
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Reverberation and Dereverberation Using an Acoustic Multiple-Input Multiple-Output System

Abstract: Methods are proposed for modifying the reverberation characteristics of sound fields in rooms by employing a loudspeaker with adjustable directivity, realized with a compact spherical loudspeaker array (SLA). These methods are based on minimization and maximization of clarity and direct-to-reverberant sound ratio. Significant modification of reverberation is achieved by these methods, as shown in simulation studies. The system under investigation includes a spherical microphone array and an SLA, comprising a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, some studies have shown that the results are not fully reproducible from one CDM to another [12] or from one center to another [13]. Some approaches argue that keeping the local conceptual model [14] and the local structural model [15] leads to better results. On the one hand, keeping MIMIC in its specific form will not solve the limitation for multicenter research, but on the other hand, a fully standardized form would introduce other disadvantages, such as loss of data and lower computational performances.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that the results are not fully reproducible from one CDM to another [12] or from one center to another [13]. Some approaches argue that keeping the local conceptual model [14] and the local structural model [15] leads to better results. On the one hand, keeping MIMIC in its specific form will not solve the limitation for multicenter research, but on the other hand, a fully standardized form would introduce other disadvantages, such as loss of data and lower computational performances.…”
Section: Introductionmentioning
confidence: 99%
“…The git repository centralizes the various resources of this work such as documentation, source code, unit tests, as well as questioning examples, discussions and problem issues. It also indicates web resources such as the physical data model for MIMIC 11 and OMOP 12 datasets and the Achilles' web client 13 . All the code to create these statistics is provided on the article's framagit repository (see Repository Work section).…”
Section: Resultsmentioning
confidence: 99%
“…All the code to create these statistics is provided on the article's framagit repository (see Repository Work section). 9 http://blogs.aphp.fr/dat-icu/ 10 https://www.softwareheritage.org/ 11 https://mit-lcp.github.io/mimic-omop/schemaspymimic 12 https://mit-lcp.github.io/mimic-omop/schemaspyomop 13 https://mit-lcp.github.io/mimic-omop/AchillesWeb…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The listening experiment followed the protocol of the established MUSHRA test (MUltiple Stimuli with Hidden Reference and Anchor) [29], but without a hidden anchor. This approach seems useful when there is no standard anchor signal for the experiment [30]. Four different MUSHRA screens were generated for each of the acoustic environments described in Table I.…”
Section: A Methodologymentioning
confidence: 99%